Answers

2014-05-20T00:14:37+05:30
Xy = c²
xdy/dx + y = 0           
dy/dx = -y/x
dy/dx = -b/a                                     {slope at point (a,b)}
equation of tangent ;
(y-b) = (-b/a)(x-a)
ay - ab = -bx + ab
bx + ay = 2ab   or
x/a + y/b = 2
0
2014-05-20T11:59:33+05:30
Xy = c²
differentiating the above curve at (a,b) we get slope of that tangent at that point
x*dy/dx + y = 0
x*dy/dx = -y
 dy/dx= -y/x
  slope at the point (a,b)
 dy/dx = -b/a
the equation of the tangent at (a,b)
(y-b) = -b/a (x-a)
a(y-b)= -b(x-a)
ay-ab = -bx +ab
bx+ay -2ab = 0 
This is equation of tangent at the point (a,b)
0